Beyond online sales: From service quality to e-loyalty and word of mouth - Acosta Morey, Karla (2023)
The purpose of this research is to demonstrate how service quality is an antecedent, influencing through trust and satisfaction, in electronic loyalty and word-of-mouth within e-commerce businesses. Data was collected from 300 users with e-commerce shopping experience and to test the proposed hypothesis the results were analysed using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results showed that service quality has a positive effect on e-satisfaction and e-trust, and these in turn influence e-loyalty and electronic word of mouth. The main contribution of this research is to expand knowledge on the relationship between service quality and word of mouth in an e-commerce environment.